2011
DOI: 10.1007/s10103-011-0901-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic therapy in the non-surgical treatment of aggressive periodontitis: microbiological profile

Abstract: The aim of this trial was to investigate changes occurring in the subgingival microbiological composition of subjects with aggressive periodontitis, treated with antimicrobial photodynamic therapy (aPDT), in a single episode, or scaling and root planing (SRP), in a split-mouth design on -7, 0, and +90 days. Ten patients were randomly assigned to either aPDT using a laser source in conjunction with a photosensitizer or SRP with hand instruments. Subgingival plaque samples were collected and the counts of 40 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 51 publications
0
50
1
14
Order By: Relevance
“…Free radicals are formed, such as oxygen species that have a toxic effect on cells. [11][12][13][14] PDT is a repeatable procedure which costs less than other methods, has a broad spectrum microbicidal effects, is safe for the host tissue, and can reach inaccessible sites. 15 Another alternative method to treat periodontal diseases is to find substances with anti-plaque effects that can inhibit bacterial reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals are formed, such as oxygen species that have a toxic effect on cells. [11][12][13][14] PDT is a repeatable procedure which costs less than other methods, has a broad spectrum microbicidal effects, is safe for the host tissue, and can reach inaccessible sites. 15 Another alternative method to treat periodontal diseases is to find substances with anti-plaque effects that can inhibit bacterial reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…without any mechanical debridement). 42,43 (Table 2). While one study has found in deep pockets (PD ≥ 7 mm) statistically significant improvements in terms of PD reduction and CAL gain and significantly less periodontal pathogens of the red and orange complex and IL-1β/IL-10 ratio following treatment with PDT, 41 the other study has failed to reveal any statistical significant differences in the evaluated clinical and microbiological parameters between the treatments 40 (Table 2).…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…2 In addition, various systemic and local chemical antimicrobial agents have been introduced for the treatment of peri-implantitis, which suppress periodontopathogens more effectively compared to mechanical techniques, and improve the results of conventional mechanical therapeutic techniques. [3][4][5][6][7] Some disadvantages of antimicrobial agents' use, (such as antibiotics) include an increase in the counts of bacteria resistant to these agents, the need for the use of different antibiotics due to the diversity of periodontopathogens, an increase in the number of immunosuppressed patients and the incidence of unfavorable reactions. Considering the complications above, it is necessary to expand research Original Article doi 10.15171/jlms.2017.25…”
Section: Introductionmentioning
confidence: 99%